Tapping Touch (Tato) sebagai Upaya Penurunan Nyeri Dismenore - Tina Mawar Dika; Umi Aniroh; Fiktina Vifri Ismiriyam Ismiriyam (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2022)
A way to support the government's efforts to provide quality health services to adolescents, especially young women, requires the involvement of health educators to conduct education about tapping touch as an effort to reduce dysmenorrhea pain. Problems that occur in adolescents during menstruation are not only related to cleanliness but also the emergence of discomfort in the abdomen which we often know as dysmenorrhea pain. Health education about tapping touch to treat dysmenorrhea pain is given to young women who are still in school where most of the students are girls so that the interventions provided are right on target. Based on the survey, it is known that the students of SMP An Nur Ungaran have never received health education about tapping touch as an effort to reduce dysmenorrhea pain. The implementation of this community service activity is carried out by the method of providing education to the students of SMP An Nur Ungaran. The percentage of evaluation results before being given education was in the category of not understanding as much as 19.95%, quite understanding 50.88%, good understanding 21.79% and very good 7.86%. The understanding of female students has increased after being given education which is included in the very good category by 35.42%, good 56.94%, 4.82% enough and 2.82% less. Thus it is known that after being given education there is an increase in female students' understanding of tapping touch as an effort to reduce dysmenorrhea pain. Based on statistical analysis (Wilcoxon test) obtained a significance value of 0.003 <0.05, which means that there is a significant difference in the level of knowledge between before and after education. about the TATO (Tapping Touch) program to treat adolescent girls with dysmenorrhea pain. The purpose of this community service activity is to teach young women to reduce the degree of dysmenorrhea pain with the tapping touch technique.ABSTRAKSuatu cara mendukung upaya pemerintah dalam memberikan pelayanan kesehatan yang berkualitas kepada remaja, khususnya pada remaja putri maka diperlukan ketelibatan tenaga pendidik bidang kesehatan untuk melakukan edukasi tentang tapping touch sebagai upaya penurunan nyeri dismenore. Permasalahan yang terjadi pada remaja saat terjadi menstruasi tidak hanya terkait tentang kebersihan tetapi juga munculnya rasa tidak nyaman pada bagian perut yang sering kita kenal dengan nyeri dismenore. Pendidikan Kesehatan tentang tapping touch untuk mengatasi nyeri disminore diberikan pada remaja putri yang masih berada di sekolah yang siswanya sebagian besar perempuan sehingga intervensi yang diberikan tepat sasaran. Berdasarkan survey diketahui bahwa siswi SMP An Nur Ungaran belum pernah mendapatkan pendidikan kesehatan tentang tapping touch sebagai upaya penurunan nyeri dismenore. Pelaksanaan kegiatan pengabdiaan kepada masyarakat ini dilakukan dengan metode pemberian edukasi pada siswa SMP An Nur Ungaran. Persentase hasil evaluasi sebelum diberikan edukasi masuk dalam kategori kurang paham sebanyak 19,95%, cukup paham 50,88 %, pemahaman yang baik 21,79% dan sangat baik 7,86%. Pemahaman siswa perempuan mengalami peningkatan setelah diberikan edukasi yaitu termasuk dalam kategori sangat baik sebesar 35,42%, baik 56,94%, cukup 4,82% dan kurang sebanyak 2,82%. Dengan demikian diketahui bahwa setelah diberikan edukasi terdapat peningkatan pemahaman siswa perempuan tentang tapping touch sebagai upaya penurunan nyeri dismenore. Berdasarkan analisis statistik (uji Wilcoxon) didapatkan nilai signifikansi 0,003 < 0,05 yang berarti terdapat perbedaan bermakna pada tingkat pengetahuan antara sebelum dan setelah edukasi. tentang program TATO (Tapping Touch) untuk mengatasi remaja putri dengan nyeri disminorea. Tujuan dari kegiatan pengabdian masyarakat berikut adalah mengajarkan kepada remaja putri untuk menurunkan derajat nyeri dysminorea dengan tehnik tapping touch